Real-Time Sonoelastography of Lateral Epicondylitis: Comparison of Findings Between Patients and Healthy Volunteers - De Zordo, Tobias; Lill, Stephanie R; Fink, Christian; Feuchtner, Gudrun M; Jaschke, Werner; Bellmann-Weiler, Rosa; Klauser, Andrea S (American journal of roentgenology (1976), 2009)
The purpose of this study was to evaluate real-time sonoelastography in the assessment of the origins the common extensor tendon in healthy volunteers and in patients with symptoms of lateral epicondylitis. The findings were compared with those obtained at clinical examination, ultrasonography, and power Doppler sonography. Thirty-eight elbows of 32 consecutively registered patients with symptoms of lateral epicondylitis and 44 asymptomatic elbows of 28 healthy volunteers were assessed with ultrasound and real-time sonoelastography. A clinical examination was performed, and pain was classified with a visual analog scale. In healthy volunteers, real-time sonoelastographic images showed hard tendon structures in 96% of tendon thirds and mild alterations in 4%. Real-time sonoelastography of patients showed hard structures in 33% of tendon thirds but softening of different grades in 67%, a statistically significant difference in relation to the findings in healthy volunteers (p < 0.001). Lateral collateral ligament involvement and overlying fascial involvement were more commonly detected with real-time sonoelastography. The sensitivity of real-time sonoelastography was 100%, the specificity 89%, and the accuracy 94% with clinical examination as the reference standard. Good correlation with ultrasound findings was found (r > or = 0.900). No correlation was observed between ultrasound or real-time sonoelastographic findings and power Doppler sonographic findings, but power Doppler sonographic findings had a strong correlation with the visual analog scale score. Real-time sonoelastography is valuable in the detection of the intratendinous and peritendinous alterations of lateral epicondylitis and facilitates differentiation between healthy and symptomatic extensor tendon origins with excellent sensitivity and excellent correlation with ultrasound findings.